Pitfalls in mutational testing and reporting of common KIT and PDGFRA mutations in gastrointestinal stromal tumors - Penzel Roland; Mechtersheimer Gunhild; Krohn Antje; Kitz Julia; Haller Florian; Gaumann Andreas; Füzesi Laszlo; Dietmaier Wolfgang; Merkelbach-Bruse Sabine; Schildhaus Hans-Ulrich; Schneider-Stock Regine; Simon Ronald; et al. (BMC, 2010)
Abstract Background Mutation analysis of KIT and PDGFRA genes in gastrointestinal stromal tumors is gaining increasing importance for prognosis of GISTs and for prediction of treatment response. Several groups have identified specific mutational subtypes in KIT exon 11 associated with an increased risk of metastatic disease whereas GISTs with PDGFRA mutations often behave less aggressive. Furthermore, in advanced GIST disease with proven KIT exon 9 mutation the doubled daily dose of 800 mg imatinib increases the progression free survival and is now recommended both in the European and the American Guidelines. In Germany, there are still no general rules how to perform mutational analysis. Methods When comparing results from six different molecular laboratories we recognized the need of standardisation. Six German university laboratories with experience in mutation analysis in GISTs joined together to develop recommendations for the mutation analysis of the most common and clinically relevant hot spots, i. e. KIT exons 9 and 11 and PDGFRA exon 18. We performed a three-phased interlaboratory trial to identify pitfalls in performing molecular analysis in GISTs. Results We developed a design for a continuous external laboratory trial. In 2009 this external trial was conducted by 19 laboratories via the initiative for quality assurance in pathology (QuiP) of the German Society of Pathology and the Professional Association of German Pathologists. Conclusions By performing a three-phased internal interlaboratory trial and conducting an external trial in Germany we were able to identify potential pitfalls when performing KIT and PDGFRA mutational analysis in gastrointestinal stromal tumors. We developed standard operation procedures which are provided with the manuscript to allow other laboratories to prevent these pitfalls.